Macroeconomic constraints to growth of Brazilian economy diagnosis and some policy proposals - Oreiro, José Luis (2016)
The recent process of accelerated expansion of the Brazilian economy was driven by exports and fixed capital formation. Although the pace of growth was more robust than in the 1990´s, we can still witness the existence of certain macroeconomic constraints to its continuation in the long run such as, for instance, the exchange rate overvaluation in particular since 2005, and in general the modus operandi of monetary policy. Such constraints may jeopardize the sustainability of the current pace of growth. Therefore, we argue that Brazil still lies in a trap made up of high interest and low exchange rates. The elimination of the exchange rate misalignment would bring about a great increase in the rate of interest, which on its turn would impact negatively upon investment and hence upon the sustainability of long run economic growth. We outline a set of policy measures to eliminate such a trap, in particular, the adoption of an implicit target for the exchange rate, capital controls and the abandonment of the present regime of inflation targeting. Recent events seem to go in this direction.